Scope definition of danger zone-moving tower cranes - Matviyevskyy, S.; Nikohosyan, N. (Ways to Improve Construction Efficiency, 2015)
This article deals with an issue of determining the hazardous area boundaries when handling loads with tower cranes, it emphasies the need to correct statement of this issue in the construction organization manuals.